2015
DOI: 10.1093/asj/sjv090
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose Tissue-Derived Stromal/Stem Cells Promote Migration and Early Metastasis of Head and Neck Cancer Xenografts

Abstract: Human ASCs did not alter growth of human head/neck cancer cells or tumor xenografts, but stimulated migration and early micrometastasis to mouse brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
2
33
2
Order By: Relevance
“…AT-MSCs promote migration and early metastasis of head/neck cancer cell lines Cal-27 and SCC-4 in vitro and in xenografts 42. AT-MSCs inhibit the growth of human melanoma cell lines (A375SM and A375P) by inducing apoptosis and altering cell-cycle distribution in vitro .…”
Section: Mscs In Anticancer Therapiesmentioning
confidence: 98%
“…AT-MSCs promote migration and early metastasis of head/neck cancer cell lines Cal-27 and SCC-4 in vitro and in xenografts 42. AT-MSCs inhibit the growth of human melanoma cell lines (A375SM and A375P) by inducing apoptosis and altering cell-cycle distribution in vitro .…”
Section: Mscs In Anticancer Therapiesmentioning
confidence: 98%
“…Stem cell reconstruction has been most extensively studied in breast cancer and remains intensely controversial . An influential mouse study with ductal breast carcinoma cells found increased metastases when MSC were administered; similar results occurred with head and neck cancer cell lines . Nonetheless, numerous conflicting animal and human studies have led to uncertainty about long‐term outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…More than 60 patients have been treated using autologous fat administration in three different studies [63][64][65]79]. Some concerns have been raised about the possibility of administered fat to promote residual tumor cell invasion and metastasis [80]. Preliminary data obtained using head and neck cancer cell lines both in vitro and in vivo suggest that the procedure may be safe, but further investigation performed on patientderived tumor samples is needed [81].…”
Section: Head and Neck Reconstruction After Radiotherapymentioning
confidence: 99%